Ethnomathematics of Darussajidin Mosque Indramayu in designing mathematics activities and philosophy of Islamic values - Mellawaty, Mellawaty; Nurhazijah, Eva; Mulyana, Diki (Universitas Papua, 2023)
A mosque is a place of worship for Muslims worldwide. The shape of the mosque in each region is different. Along with the times, the mosque has also become one of the objects in cultural acculturation from one area to another, thus creating increasingly diverse shapes and designs in mosques. One of them is the Darussajidin Mosque in Bondan Barat Indramayu. This research aims to determine the ethnomathematics of the Darussajidin Indramayu mosque in designing mathematical activities and the ethnomathematics of the Darussajidin Indramayu mosque on the philosophical meaning of Islamic values. This research was conducted at the Darussajidin mosque, Indramayu, in Bondan Village, Sukagumiwang District, Indramayu Regency. The subjects in this study were DKM mosques, caretakers, community leaders, and cultural observers, while the object in this study was the Darussajidin Indramayu mosque. This research is qualitative research with an ethnographic approach. Observation, interviews, and documentation collected data. The instruments used are observation guidelines, interview guidelines, and documentation tools. The results showed that there was ethnomathematics of the Darussajidin Indramayu mosque in the mathematical activity of designing, and there was ethnomathematics of the Darussajidin Indramayu mosque in the philosophical meaning of Islamic values among them; on the roof, dome, walls, pillars, floors, and ornaments of the Darussajidin Indramayu mosque.